Penyelesaian Sengketa Wanprestasi di BMT Al-Hidayah - Abdul Hafiz; Habiburrahman Habiburrahman (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Baitul Maal Wat Tamwil and its customers have a very close legal relationship in which reciprocal rights and obligations arise. If in the future there is a dispute between the BMT institution and its customers, the dispute must be resolved in the fairest way. This is the right way for BMT institutions to maintain the empowerment of their customers so that they are truly protected by their rights. This study aims to find out how to resolve default disputes in BMT Al-Hidayah. The method used in this study is qualitative research method. This research is included in the category of case study research using a qualitative approach that is descriptive. BMT problems are default disputes that affect the bad financing of BMT operations, bad loans and pristiwa outside of the creditor's intentionality. The default dispute resolution strategy at BMT Al-Hidayah is through litigation and non-litigation channels. This occurs in the dispute between party K and party Z, both of whom experience default disputes but in the settlement have different solutions in the resolution. Party K resolves its default disputes through familial channels and deliberation by referring to the clauses of Article 4 of Law No. 42 of 1996. Meanwhile, party Z takes dispute resolution through mediation channels involving third parties as mediators whose job is to provide solutions, direction and foresight to the problems faced. For this reason, BMT as a sharia-based institution has many alternatives and appropriate strategies in solving disputes that occur.